2020
DOI: 10.1111/acer.14492
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Genetic Variants Associated With Alcohol Dependence and Related Phenotypes Using a High‐Throughput Assay

Abstract: Background: Genome-wide association studies (GWAS) of alcohol dependence (AD) and related phenotypes have identified multiple loci, but the functional variants underlying the loci have in most cases not been identified. Noncoding variants can influence phenotype by affecting gene expression; for example, variants in the 3 0 untranslated regions (3 0 UTR) can affect gene expression posttranscriptionally. Methods: We adapted a high-throughput assay known as PASSPORT-seq (parallel assessment of polymorphisms in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Studying populations of different ancestry, and thereby different linkage disequilibrium patterns can help narrow a locus. High throughput assays that identify functional SNPs are important methods for prioritizing SNPs for further study [21][22][23]. Identification of the functional SNP(s) and the gene or genes they affect provides a strong basis for studying the biology underlying the trait.…”
Section: What Is a "Meaningful" Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studying populations of different ancestry, and thereby different linkage disequilibrium patterns can help narrow a locus. High throughput assays that identify functional SNPs are important methods for prioritizing SNPs for further study [21][22][23]. Identification of the functional SNP(s) and the gene or genes they affect provides a strong basis for studying the biology underlying the trait.…”
Section: What Is a "Meaningful" Effect?mentioning
confidence: 99%
“…Open chromatin and potential binding sites for regulatory proteins can be identified by techniques such as ATAC-sequencing [22]. High throughput assays of SNP function (as promoters, enhancers, silencers, and modifiers of RNA stability) [21][22][23] can make important contributions. Many of these approaches have been carried out in bulk tissues, and those studies have shown the importance of tissue-specific effects.…”
Section: Finding Functional Variantsmentioning
confidence: 99%
“…It is estimated that 40-60% of AUD risk can be attributed to hereditary factors, with the remainder being linked to individual physiopsychological features, social contextual variables and gene-environment interactions [6]. Long-lasting changes in the expression of brain protein-coding genes have been the most intensively studied in AUD patients and rodents [8,9]. However, these genes only accounted for less than 2% of the mammalian genome sequence, and the rest of genomic transcripts are noncoding RNAs (ncRNAs) that were previously assumed to be incapable of coding for proteins [10].…”
Section: Ivyspringmentioning
confidence: 99%
“…Furthermore, for these disease-causing genes, it is highly likely that there is at least one disease-causing variant located within the gene boundaries, e.g. non-synonymous mutations that change gene products or 3' UTR variants that alter gene expression levels (23,24).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%